Atypical dermatological manifestations of Lyme borreliosis - Trevisan, G... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Lyme borreliosis (LB) is a multisystemic infectious disease involving the skin, joints, nervous system, heart, and eyes. Today at least three subtypes pathogenic for humans have been identified: Borrelia burgdorferi sensu stricto, Borrelia garini, Borrelia afzelii. Different genospecies strains of Borrelia have been associated with different clinical manifestations. LB is classically described as having three clinical stages or, similarly to syphilis, an early phase and a late one. The early infection corresponds to the first stage, the late infection includes the second and the third stages. LB skin manifestations could be divided into five classes. Erythema migrans, lymphadenosis benigna cutis, and acrodermatitis chronica atrophicans are proven skin manifestations of LB. Lichen sclerosus et athrophicus, morphea, scleroderma, scleredema Buschke, atrophodermia of Pierini and Pasini, Parry-Romberg progressive facial hemiatrophy, and Shulman fasciitis are controversial LB manifestations. Granuloma annulare, atypical persistent pityriasis rosea, and pityriasis lichenoides are skin lesions occasionally related to LB. Urticaria, erythema nodosum, and papular acrodermatitis (Giannotti Crosti disease) are reactive LB skin manifestations. Nodular panniculitis (Pfeifer-Weber-Christian), B-cell cutaneous lymphoma, and juvenile chronic myeloid leukemia are exceptional skin manifestations of LB.
Keywords: Borrelia burgdorferi; Kožne manifestacije; Lyme disease; Lymska bolezen sin Lymska borelioza; Skin manifestations